Mallory Weis syndrome - Valls, Alberto; Estapé, Gonzalo (Cirugía del Uruguay, 1974)
The problem of the Mallory Weiss syndrome, origined in postemetic gastroesophgeal lacerations is shown. After copius vomiting important hemorrhages appear for which the treatment is essentially surgical. Two patients treated by suture of their gastric fissure are reported. The second one recovered with this only therapeutics the first one bled throu.gh his esophageal fissure after the operation. These hemorrhages diminished with the placement of Blakemore-Sengstaken Cube, by means of which the patient was saved. The urgent surgical therapeutics have come as far as the total gastrectomy